2012
DOI: 10.1097/cmr.0b013e32834defec
|View full text |Cite
|
Sign up to set email alerts
|

The value of cyclooxygenase-2 expression in differentiating between early melanomas and histopathologically difficult types of benign human skin lesions

Abstract: Early cutaneous melanomas may present a substantial diagnostic challenge. We have already reported that expression of cyclooxygenase-2 (COX-2) may be useful for differentiating between cutaneous melanomas and naevi. The purpose of this study was to examine the value of COX-2 in a challenging task of differential diagnosis of early melanomas and melanocytic naevi considered by histopathologists as morphologically difficult to unequivocally diagnose as benign lesions. The material for the study comprised formali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 23 publications
4
23
0
Order By: Relevance
“…When all tumour samples were considered, including malignant and benign melanocytic tumours, COX-2 immunoexpression presented associations with proliferation, angiogenesis and immune infiltration biomarkers. This heterogeneous group of tumours might have skewed the analysis as melanocytomas tend to have lower COX-2 expression [14,15] and naturally reduced proliferation and angiogenesis compared with the malignant melanomas, as confirmed in our results.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…When all tumour samples were considered, including malignant and benign melanocytic tumours, COX-2 immunoexpression presented associations with proliferation, angiogenesis and immune infiltration biomarkers. This heterogeneous group of tumours might have skewed the analysis as melanocytomas tend to have lower COX-2 expression [14,15] and naturally reduced proliferation and angiogenesis compared with the malignant melanomas, as confirmed in our results.…”
Section: Discussionsupporting
confidence: 87%
“…Also, the fact that COX-2 expression was found to be absent in cutaneous melanocytomas, but present in malignant cutaneous melanomas, suggests that COX-2 may be associated with the acquisition of malignancy during the tumorigenesis of melanocytic neoplasms [14]. Similarly, in human cutaneous melanomas, COX-2 expression has been proposed as a new biomarker to help pathologists distinguish benign melanocytic lesions from early malignant melanomas [15].…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, cutaneous melanomas and compound melanocytic nevi showed similar results, as also observed by Denkert et al and Bianchini et al . Kuzbicki et al demonstrated that the immunohistochemical intensity of COX‐2 is associated with Clark level and Breslow thickness, suggesting this protein as a molecular prognostic marker. We also found a single case of cutaneous melanoma with Clark level III and Breslow thickness >2 mm exhibiting high COX‐2 positivity, but this finding was different from those found in oral melanomas, in which both invasive and in situ lesions showed high positivity for COX‐2.…”
Section: Discussionsupporting
confidence: 75%
“…Currently, there is little evidence to claim that oral melanocytic nevi increases the risk for oral melanomas, but the development of melanomas has been attributed of being preceded by pigmented lesions of unknown characteristics . Kuzbicki et al showed COX‐2 positive cells only occasionally in benign melanocytic lesions, particularly in dysplastic nevi. It would be interesting to determine COX‐2 expression in atypical melanocytic hyperplasias of the oral cavity, but considering their rarity, multicentric studies are encouraged for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 may be a reasonable target in melanoma, as it is generally not expressed in benign melanocytic nevi but is highly expressed in most melanomas (41, 42). Analysis of primary and metastatic melanoma lesions revealed increased COX-2 expression with melanoma progression (43), and that high COX-2 expression correlates inversely with patient survival (44).…”
Section: Nsaid Mechanism Of Action and Rationale For Use In Melanoma mentioning
confidence: 99%